Alien and invasive species in plant communities of the Vistula and Brennica rivers gravel bars (Western Carpathians, Poland) - Wilczek, Zbigniew; Chabowska, Zuzanna; Zarzycki, Wojciech (Biodiversity: Research and Conservation, 2015)
Gravel bars are the initial habitats, inseparably connected to the mountain streams. On the one hand, they are an unstable substrate, influenced by the overflows and high waters; however, they are also exposed to strong sunlight and heat. This situation determines specific vegetation which, due to dynamic changes in the habitat, has a pioneer character. What is more, gravel bars are areas where many river migratory species and many random species appear. Among them, there are also synanthropic species. In years 2011-2012, floristic and phytosociological studies were conducted in the Silesian Beskids. The goal of these studies was to recognize the vegetation of the gravel bars of the Vistula and the Brennica rivers - from their springs in the Silesian Beskids to the point where the Brennica River flows into the Vistula River in the Silesian Foothills. The studied section of the two rivers is regulated. Particular attention was paid to the synanthropic species that pose a threat to the native flora. In 9 recognized types of plant communities, 293 vascular plant species were recognized. More than 15% of the flora were alien species (45) and 22 of them were considered to be invasive. The most common invasive species that were spotted included: Impatiens glandulifera, Heracleum mantegazzianum and Reynoutria japonica. Plant communities with the biggest number and share of alien species were Plantago major-Barbarea vulgaris community and Phalaridetum arundinaceae.